Peningkatan Keterampilan Menulis Teks Drama melalui Model Project-Based Learning Berbantuan Media Flipbook pada Siswa Kelas XI TPK SMK - Nesy Indiasty; M. Faisal Rochmans; Dwi Setia Ningrum; Agung Pramujiono (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This classroom action research aims to improve the drama script writing skills of Grade XI TPK students at SMK Negeri 3 Buduran Sidoarjo through the implementation of the Project-Based Learning (PjBL) model assisted by flipbook media. The study was conducted in two cycles, each comprising the stages of planning, action, observation-evaluation, and reflection. The research subjects consisted of 35 students. Data were collected through observation, drama script writing tests, and student response questionnaires. The results showed that in the pre-cycle stage, only 26.8% of students reached the minimum mastery criteria, with an average score of 55.2. After the application of PjBL and flipbook media, significant improvements were observed in Cycle I (65.7% mastery, average score of 70.4) and Cycle II (86.5% mastery, average score of 82.3). The use of PjBL supported by flipbook media proved effective in enhancing students' writing quality in terms of dramatic structure, character development, dialogue, as well as increasing motivation and active participation in the learning process. This study recommends the use of interactive digital media and project-based approaches in teaching creative writing in vocational schools.